Defining the Role of Competition in the Airport Industry: A Critical Assessment - Polemis, Michael L.; Oikonomou, Aikaterina (Journal of Reviews on Global Economics, 2016)
Defining the relevant market is a preliminary step in every assessment of the degree of Significant Market Power (SMP). A firm with total market power can raise prices without losing any customers to competitors. SMP exists when prices exceed marginal cost and long run average cost, so the firm makesÂ economic profits. The contribution of this paper is two-fold. On the one hand, a critical assessment of the role of competition in an industry/sector is performed. To this end, we discuss the most recent quantitative and qualitative techniques in market delineation. On the other hand, we try to shed some light on the competitive constraints in the Cypriot airport industry where little prior knowledge is evident. Although the airport industry is a crucial economic sector and has oligopolistic, to some extent even monopolistic structure, there is no standard and universal approach established by the National Competition Authorities (NCAs) for exact categorization of market delineation. Î¤his paper tries to perform a thorough market power assessment in order to analyse all the competitive constraints faced by an airport operator, regardless of whether they arise from within or outside the relevant market(s).